Analyzing students’ concentration in online courses through Webcam - Asif, Md.; Hossain, Md. Imtiaj; Sharkar, Fouzia; Islam, Md. Mohaimenul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.